Caracterización de las empresas familiares de alimentos en la ciudad de Bogotá (2015)
The present articles, specification sheets of the sector have as intention elaborate food of the city of Bogota D.C and its implementation. For the study one worked with fourteen (14) family companies located in different sites of the city and distributed by economic activity made through convenience sampling as follow: A bakery; a producer of fried; a supplier of food; a fish; an international distributor of food; an ice cream factory; six restaurants; a producer of wafers and juice.